Self-inflicted partial epiphyseolysis of the distal femur—a case report - Anna Kanewska; Johannes Krause; Mario Perl (Frontiers in Pediatrics)
IntroductionInjuries to the epiphyseal plate are of great concern as they can affect bone growth. Although epiphyseal fractures are common in adolescents, fractures of the distal femoral epiphyseal plate are rare.Case presentationWe present a case of a Salter–Harris type 1 fracture of the distal epiphysis of the femur that was self-inflicted by a patient with paraplegia due to spina bifida. The patient was brought to the pediatrician's attention during a routine checkup with an apparent swelling of the right thigh. Upon presentation, we performed a radiograph and an additional MRI, which revealed a partial ventero-medial epiphyseolysis, consistent with a Salter–Harris type 1 fracture. Due to the dislocation, we indicated closed reduction with K-wires. Repositioning was performed using a modified Kapandji maneuver and was completed with additional K-wires.ConclusionDistal epiphyseolysis is a relatively rare injury that can lead to serious complications. Therefore, although rare, epiphyseal fractures should be considered in pediatric patients presenting with uncertain limb swelling.